Art And Exceptionality: Addressing Art Fear And Fear Of Difference In An Introductory Art Course - Hochman, Arthur; Esteves, Kelli J. (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2021)
Abstract: University educators designed and co-taught a course which involved collaborative artmaking and learning with a community-based arts organization that serves individuals with disabilities.  Their goal was to help university students examine the potential of art and how it applies to their personal and professional lives. They sought to better understand how to nurture a feeling of artistic agency in undergraduate students who do not define themselves as artists. Educators found that students benefited from an exploration of art fear through an inclusive approach to art creation.